Composite nucleating agent and application, nylon material and preparation method thereof

CN122958764APending Publication Date: 2026-10-23NINGBO XINGRUI ENERGY TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611268697.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-23

AI Technical Summary

Benefits of technology

(1)本发明的复合成核剂由芳香族酰胺成核剂与有机改性蒙脱土复配而成。其协同作用机理如下:晶态结构优化(主成核):芳香族酰胺成核剂作为主成核组分,通过高效的异相成核效应,大幅细化尼龙球晶尺寸并促进晶区均匀分布。这有效压缩了无定形区的连续扩散通道,减少了大晶界处的内应力缺陷,从而从晶态维度显著降低了碱液的渗透速率与晶界侵蚀风险。双重屏障构建(辅助成核):有机改性蒙脱土作为双功能辅助成核剂,一方面以其纳米硅酸盐片层提供额外的异相晶核位点,与主成核剂协同提升晶核密度,进一步强化晶区的致密性;另一方面,其通过剥离分散的二维纳米片层在基体中构建出曲折的扩散路径,大幅延长了KOH等电解液的渗透时间,形成核心耐碱屏障,从而全面提升尼龙材料在强碱环境下的长效稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of high polymer material modification, and discloses a composite nucleating agent and application, a nylon material and a preparation method of the nylon material. The composite nucleating agent comprises aromatic nucleating agents and organic modified montmorillonite with a mass ratio of (2-4):1. The nylon material comprises, in terms of weight parts, 80-95 parts of a matrix resin, 0.3-2 parts of an epoxy chain extender, 0.2-1 part of an alkali-resistant stabilizer and 0.5-3 parts of the composite nucleating agent; the matrix resin is a blend of long carbon chain nylon and semi-aromatic nylon with a mass ratio of (85-95):(5-15). Through the synergistic effect of nucleation crystallization and nano barrier, the nylon material has excellent mechanical properties, high load heat deformation temperature and excellent alkali corrosion resistance by in-situ chain extension and rigidity increase, and is suitable for preparing sealing and insulating components of alkaline-manganese batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a composite nucleating agent and its application, and also to a nylon material and its preparation method. Background Technology

[0002] Alkaline manganese batteries are widely used primary batteries in civilian and industrial electronic devices, employing a strongly alkaline KOH electrolyte. Furthermore, alkaline manganese batteries often face high-temperature environments during storage, transportation, and high-power discharge. Currently, structural components such as seals and insulating gaskets in alkaline manganese batteries are mostly made of long-chain nylon (Nylon 612, Nylon 610). While these materials have excellent alkali resistance, their heat distortion temperature under load is relatively low, making them prone to thermal deformation under high-temperature conditions. This can lead to battery leakage and insulation failure, making them unsuitable for high-temperature storage and high-power discharge.

[0003] Conventional modification methods for improving the heat resistance of nylon still have significant shortcomings. For example, glass fiber reinforcement reduces material toughness and increases surface roughness, making it difficult to meet the precision dimensional accuracy and sealing elasticity requirements of battery seals. While semi-aromatic high-temperature resistant nylons (PA6T, PA9T) have outstanding heat resistance, their raw material costs are high, and their alkali resistance and injection molding performance are weaker than long-chain nylons, hindering their large-scale application in alkaline manganese batteries. Meanwhile, most existing modification schemes primarily aim to improve the dry-state heat resistance of materials, without specifically addressing the service environment of concentrated KOH strong alkalis. Therefore, the industry urgently needs to develop a modified nylon material that combines high heat distortion temperature, excellent alkali resistance, and controllable cost.

[0004] CN108587147A discloses a nylon 6 composition, its preparation method, and its application. The raw materials include nylon 6, a nucleating agent, and a lubricant. The nucleating agent comprises 0.01–0.5% of the raw materials by mass percentage, and includes both organic and inorganic nucleating agents, with a mass ratio of organic to inorganic nucleating agent of 1:(1–5). The lubricant comprises 0.05–1.0% of the raw materials by mass percentage. This invention controls the crystallization process through the compounding of organic and inorganic nucleating agents and lubricant, solving the problem of slow crystallization and long molding cycles in nylon 6 during injection molding, which makes it difficult to meet the requirements of large-scale production. It does not address the alkali resistance and heat distortion temperature of nylon. Summary of the Invention

[0005] In view of this, one object of the present invention is to provide a composite nucleating agent that can increase the heat distortion temperature of nylon materials and improve the alkali resistance of nylon materials.

[0006] Another objective of this invention is to provide an application of the above-mentioned composite nucleating agent in improving the heat distortion temperature and alkali resistance of nylon materials, especially in nylon materials used to prepare sealing and insulating components for alkaline manganese batteries.

[0007] Another object of the present invention is to provide a nylon material having a high heat distortion temperature and good alkali resistance.

[0008] Another objective of this invention is to provide a method for preparing the above-mentioned nylon material, which has a simple process, is easy to operate, and produces nylon material with excellent comprehensive mechanical properties, high heat distortion temperature under load, and excellent alkali corrosion resistance.

[0009] On one hand, the present invention provides a composite nucleating agent comprising an aromatic nucleating agent and an organically modified montmorillonite, wherein the mass ratio of the aromatic nucleating agent to the organically modified montmorillonite is (2-4):1.

[0010] In the preparation of alkali-resistant nylon materials, existing technologies typically employ organic nucleating agents to increase crystallinity and delay alkali penetration. However, such methods offer limited improvement in alkali resistance, and excessively high crystallinity exacerbates material brittleness, leading to stress cracking after alkali etching, making it difficult to balance toughness and long-term corrosion resistance. On the other hand, conventional inorganic nucleating agents, due to their large particle size and weak interfacial bonding with the nylon matrix, easily form penetration defect channels within the material; during long-term immersion in a strongly alkaline environment, the interface is prone to deterioration, resulting in a significant decrease in the material's mechanical properties and processing fluidity. The composite nucleating agent of this invention is a compound of an aromatic amide nucleating agent and organically modified montmorillonite. Its synergistic mechanism is as follows: Crystal structure optimization (main nucleation): Aromatic amide nucleating agent, as the main nucleating component, significantly refines the size of nylon spherulites and promotes uniform distribution of crystalline regions through efficient heterogeneous nucleation. This effectively compresses the continuous diffusion channels in amorphous regions and reduces internal stress defects at large grain boundaries, thereby significantly reducing the penetration rate of alkali solution and the risk of grain boundary erosion from a crystalline perspective.

[0011] Dual Barrier Construction (Assisted Nucleation): Organically modified montmorillonite, as a bifunctional assisted nucleating agent, provides additional heterogeneous nucleation sites through its nano-silicate sheets, synergistically enhancing the nucleation density with the main nucleating agent and further strengthening the compactness of the crystal region. On the other hand, it constructs a tortuous diffusion path in the matrix by peeling off the dispersed two-dimensional nanosheets, significantly extending the penetration time of electrolytes such as KOH, forming a core alkali-resistant barrier, thereby comprehensively improving the long-term stability of nylon materials in strong alkaline environments.

[0012] According to the composite nucleating agent of the present invention, preferably, the aromatic nucleating agent is selected from at least one of aromatic amide nucleating agents and aromatic acylhydrazine nucleating agents; the organic modified montmorillonite may be selected from at least one of organic ammonium modified montmorillonite, amino acid modified montmorillonite, and polymer intercalated modified montmorillonite.

[0013] According to the composite nucleating agent of the present invention, preferably, the aromatic amide nucleating agent is selected from at least one of 1,3,5-benzenetricarboxamide (TCBT), aromatic diamide, and monoaromatic amide; wherein, the aromatic diamide is selected from at least one of N,N'-dicyclohexylterephthalamide (DCHT) and N,N'-dicyclohexyl-2,6-naphthalenediamide; and the aromatic acylhydrazine nucleating agent is a bisbenzoylhydrazine nucleating agent (DABH).

[0014] In this invention, the aromatic nucleating agent may be selected from at least one of aromatic amide nucleating agents and aromatic acyl hydrazide nucleating agents; preferably at least one of 1,3,5-benzenetricarboxamide (TCBT), aromatic diamide, monoaromatic amide, and bisbenzoyl hydrazide nucleating agent (DABH); more preferably 1,3,5-benzenetricarboxamide (TCBT), N,N'-dicyclohexylterephthalamide (DCHT), or bisbenzoyl hydrazide nucleating agent (DABH).

[0015] According to some preferred embodiments of the present invention, the aromatic nucleating agent is selected from at least one of TCBT, DCHT, and DABH. The nylon thus produced exhibits both good alkali resistance and mechanical properties.

[0016] In this invention, the organically modified montmorillonite is a commercially available industrial product. The organically modified montmorillonite can be selected from at least one of organoammonium-modified montmorillonite, amino acid-modified montmorillonite, and polymer-intercalated modified montmorillonite; preferably, it is organoammonium-modified montmorillonite.

[0017] According to some preferred embodiments of the present invention, the organically modified montmorillonite is selected from at least one of the DK2, DK1N or DK5 series of organic ammonium modified montmorillonite.

[0018] According to the composite nucleating agent of the present invention, preferably, the composite nucleating agent is composed of the aromatic nucleating agent and the organically modified montmorillonite.

[0019] According to some preferred embodiments of the present invention, the composite nucleating agent is composed of the aromatic nucleating agent and the organic modified montmorillonite, and the mass ratio of the aromatic nucleating agent to the organic modified montmorillonite is (3-4):1. The composite nucleating agent prepared in this way can further improve the heat distortion temperature of nylon materials and improve the alkali resistance of nylon materials.

[0020] On the other hand, this invention provides an application of the aforementioned composite nucleating agent, which can be used to increase the heat distortion temperature of nylon materials and improve their alkali resistance. This nylon material can be used to prepare sealing and insulating components for alkaline manganese batteries, such as sealing rings for alkaline manganese batteries.

[0021] In another aspect, the present invention provides a nylon material, which, by weight, comprises: 80-95 parts of matrix resin, 0.3-2 parts of epoxy chain extender, 0.2-1 parts of alkali-resistant stabilizer, and 0.5-3 parts of the composite nucleating agent; The matrix resin is a blend of long-chain nylon and semi-aromatic nylon in a mass ratio of (85-95):(5-15); the long-chain nylon is selected from at least one of nylon 612 and nylon 610; the semi-aromatic nylon is selected from at least one of poly(hexamethylene terephthalamide) (PA6T), poly(hexamethylene terephthalamide) / poly(hexamethylene adipamide) copolymer (PA6T / 66 copolymer), and poly(hexamethylene terephthalamide) / poly(hexamethylene isophthalamide) copolymer (PA6T / 6I copolymer).

[0022] According to some embodiments of the present invention, the raw material components of the nylon material, by weight, include: 85-90 parts of matrix resin, 1-2 parts of epoxy chain extender, 0.2-0.5 parts of alkali-resistant stabilizer, and 2-2.5 parts of the composite nucleating agent.

[0023] In this invention, the matrix resin is a blend of long-chain nylon and semi-aromatic nylon. The mass ratio of long-chain nylon to semi-aromatic nylon can be (85-95):(5-15); preferably (85-90):(5-10). On the one hand, long-chain nylon has the advantages of excellent alkali resistance, low water absorption, high toughness, and excellent injection molding flowability, but it has poor heat resistance and is prone to creep under high temperature storage and discharge conditions, leading to sealing failure. Semi-aromatic nylon has the advantages of high rigidity, high heat resistance, and strong deformation resistance, but it has poor alkali resistance and high cost. Blending the two can simultaneously meet the requirements of super alkali resistance, low water absorption and dimensional stability, improved heat resistance, and precision injection molding. On the other hand, long-chain nylon has good compatibility with the organic modified montmorillonite in the composite nucleating agent of the present invention, and can achieve layer-by-layer exfoliation and dispersion to form a highly efficient nano barrier structure; semi-aromatic nylon has a similar structure to the aromatic nucleating agent in the composite nucleating agent of the present invention, with higher nucleation efficiency and better grain refinement effect. The synergy of the two can amplify the "crystal densification and nano-physical barrier" effect.

[0024] In this invention, the long-chain nylon is selected from at least one of nylon 612 and nylon 610; preferably nylon 612. The semi-aromatic nylon is selected from at least one of PA6T, PA6T / 66 copolymer, and PA6T / 6I copolymer; preferably PA6T, PA6T / 66 copolymer, or PA6T / 6I copolymer.

[0025] In this invention, the epoxy chain extender is selected from at least one of bisphenol A type epoxy resin and styrene-glycidyl methacrylate copolymer (SAG); preferably, it is styrene-glycidyl methacrylate copolymer. This invention uses bisphenol A type epoxy resin and / or styrene-glycidyl methacrylate copolymer (SAG) as epoxy chain extenders for nylon materials. The aforementioned chain extenders are all rich in highly reactive epoxy groups (i.e., the three-membered oxygen ring structure in the glycidyl group). Under the high temperature and shearing action of extrusion processing, the epoxy groups undergo ring-opening and react with two types of end groups of nylon: one is a main reaction with the terminal amino group (-NH2), that is, the epoxy three-membered ring breaks, and the carbon atom combines with the nitrogen atom of the amino group to generate a secondary amine structure and a side hydroxyl group. This reaction is highly reactive and is the main pathway for chain extension and thickening, which can be completed quickly during processing; the other is a side reaction with the terminal carboxyl group (-COOH), that is, after the epoxy ring opens, it forms an ester bond with the carboxyl group and generates a hydroxyl group. This reaction rate is slightly slower and proceeds gradually in a high-temperature melt environment, helping to improve the degree of chain extension. It can be seen that the present invention constructs a slightly branched structure at the molecular chain level through the in-situ chain extension reaction of epoxy chain extenders with nylon; this structure, combined with the crystal refinement effect induced by the composite nucleating agent, realizes a dual stiffening mechanism of "molecular chain-crystalline state". This not only endows the material with resistance to strong alkali corrosion, but also synergistically improves the material's heat distortion temperature.

[0026] In this invention, the alkali-resistant stabilizer is a compound of hindered phenolic antioxidant and copper salt stabilizer; preferably, it is a compound formed by hindered phenolic antioxidant and copper salt stabilizer in a mass ratio of 1:(1-2).

[0027] According to the nylon material of the present invention, preferably, the epoxy chain extender is selected from at least one of bisphenol A type epoxy resin and styrene-glycidyl methacrylate copolymer; The alkali-resistant stabilizer is a compound formed by hindered phenolic antioxidant and copper salt stabilizer in a mass ratio of 1:(1-2).

[0028] In this invention, the hindered phenolic antioxidant can be selected from at least one of antioxidant 1790, antioxidant 1098, and antioxidant MD-1024; preferably antioxidant 1098. The copper salt stabilizer can be selected from at least one of Brügmann H3336, Brügmann H3337, Finner-336, and SH3360; preferably Brügmann H3336.

[0029] The nylon material according to the present invention preferably further includes 0.1 to 0.8 parts of a processing aid; the processing aid is selected from at least one of calcium stearate, zinc stearate, silicone, pentaerythritol stearate, and ethylene bis-stearamide.

[0030] In this invention, the processing aid is selected from at least one of calcium stearate, zinc stearate, silicone, pentaerythritol stearate (PETS), and ethylene bis-stearamide; preferably at least one of pentaerythritol stearate and silicone; more preferably a compound of pentaerythritol stearate and silicone.

[0031] According to some embodiments of the present invention, the processing aid is a compound formed by pentaerythritol stearate and silicone in a mass ratio of 1:(1-2).

[0032] According to some embodiments of the present invention, the raw materials of the nylon material, by weight, consist of the following components: 85-90 parts of matrix resin, 1-2 parts of epoxy chain extender, 0.2-0.5 parts of alkali-resistant stabilizer, 2-2.5 parts of composite nucleating agent, and 0.1-0.8 parts of processing aid.

[0033] According to some preferred embodiments of the present invention, the raw material components of the nylon material, by weight, include: 80-95 parts of matrix resin, 0.3-2 parts of epoxy chain extender, 0.2-1 parts of alkali-resistant stabilizer, 0.5-3 parts of composite nucleating agent, and 0.5-0.8 parts of processing aid.

[0034] Furthermore, the present invention also provides a method for preparing the above-mentioned nylon material, comprising the following steps: (1) The composite nucleating agent, alkali-resistant stabilizer and dried matrix resin are mixed to obtain a premix; (2) The premixed material is added from the main feed port of the twin-screw extruder, and the epoxy chain extender is added from the side feed port of the twin-screw extruder. After melt blending, the mixture is extruded, water-cooled, and pelletized to obtain nylon material.

[0035] According to the method for preparing nylon material of the present invention, preferably, the moisture content of the dried matrix resin is ≤0.15%; the temperature of each section of the twin-screw extruder is independently 180-250°C, and the screw speed is 200-350 rpm.

[0036] According to the method for preparing nylon material of the present invention, preferably, step (1) is carried out in a high-speed mixer with a speed of 300-500 rpm and a mixing time of 5-10 min.

[0037] The method for preparing nylon material according to the present invention preferably further includes the following steps: subjecting the matrix resin to vacuum drying to obtain the dried matrix resin, wherein the vacuum drying temperature is 80-100°C and the vacuum drying time is 4-8 hours.

[0038] According to the method for preparing nylon material of the present invention, preferably, the side feed port is located in the venting section or mixing section area downstream of the melting section of the twin-screw extruder.

[0039] According to some embodiments of the present invention, the twin-screw extruder includes six sections: a feeding section, a compression section, a melting section, a venting section, a mixing section, and a metering section. In step (2), the epoxy chain extender is added in stages from the side feed port of the fourth section (venting section) and / or the fifth section (mixing section) of the twin-screw extruder. This can effectively avoid problems such as excessively high melt viscosity, poor plasticization, and material carbonization caused by premature over-reaction of the chain extender; at the same time, it can precisely control the degree of in-situ chain extension reaction, so that the nylon molecular chains grow moderately and form a uniform, slightly branched structure. Combined with the grain-refining effect of the composite nucleating agent of the present invention, it can improve the high-temperature rigidity and dimensional stability of the material from both the molecular structure and crystal morphology dimensions. Moreover, the reaction conditions are mild throughout the process, which can maximize the preservation of the alkali resistance and toughness of the long carbon chain nylon substrate.

[0040] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite nucleating agent of the present invention is composed of an aromatic amide nucleating agent and an organically modified montmorillonite. Its synergistic mechanism is as follows: Crystal structure optimization (main nucleation): The aromatic amide nucleating agent, as the main nucleating component, significantly refines the size of nylon spherulites and promotes uniform distribution of crystalline regions through efficient heterogeneous nucleation effect. This effectively compresses the continuous diffusion channels of amorphous regions and reduces internal stress defects at large grain boundaries, thereby significantly reducing the penetration rate of alkaline solutions and the risk of grain boundary erosion from the perspective of crystal structure. Dual barrier construction (auxiliary nucleation): The organically modified montmorillonite, as a bifunctional auxiliary nucleating agent, provides additional heterogeneous nucleation sites with its nano-silicate sheets, synergistically increasing the nucleation density with the main nucleating agent and further strengthening the compactness of the crystalline regions; on the other hand, it constructs a tortuous diffusion path in the matrix by peeling off the dispersed two-dimensional nanosheets, significantly prolonging the penetration time of electrolytes such as KOH, forming a core alkali-resistant barrier, thereby comprehensively improving the long-term stability of nylon materials in strong alkaline environments.

[0041] (2) The nylon material of the present invention uses a blend of long-chain nylon and semi-aromatic nylon as the matrix resin. On the one hand, long-chain nylon has the advantages of excellent alkali resistance, low water absorption, high toughness and excellent injection molding flow, but it has poor heat resistance and is prone to creep under high temperature storage and discharge conditions, which leads to failure of sealing surface adhesion; semi-aromatic nylon has the advantages of high rigidity, high heat resistance and strong deformation resistance, but it has poor alkali resistance and high cost. The blending of the two can simultaneously meet the requirements of super alkali resistance, low water absorption and dimensional stability, improved heat resistance and precision injection molding. On the other hand, long-chain nylon has good compatibility with the organic modified montmorillonite in the composite nucleating agent of the present invention, which can achieve layer-by-layer peeling dispersion and form a highly efficient nano barrier structure; semi-aromatic nylon has a similar structure to the aromatic nucleating agent in the composite nucleating agent of the present invention, with higher nucleation efficiency and better grain refinement effect. The synergy of the two can amplify the "crystal region densification and nano-physical barrier" effect.

[0042] (3) The nylon material of the present invention uses bisphenol A type epoxy resin and / or styrene-glycidyl methacrylate copolymer (SAG) as epoxy chain extenders. The above chain extenders are all rich in highly reactive epoxy groups (i.e., the three-membered oxygen ring structure in the glycidyl group). Under the high temperature and shear action of extrusion processing, the epoxy groups undergo ring opening and react with two types of end groups of nylon: one is the main reaction with the terminal amino group (-NH2), that is, the epoxy three-membered ring breaks, the carbon atom combines with the nitrogen atom of the amino group to generate a secondary amine structure and side hydroxyl groups. This reaction is highly reactive and is the main path of chain extension and thickening, which can be completed quickly during processing; the other is the side reaction with the terminal carboxyl group (-COOH), that is, after the epoxy ring opens, it forms an ester bond with the carboxyl group and generates hydroxyl groups at the same time. This reaction rate is slightly slower and proceeds gradually in the high temperature melt environment, which helps to improve the degree of chain extension. As can be seen, this invention constructs a slightly branched structure at the molecular chain level through the in-situ chain extension reaction of epoxy chain extenders and nylon. This structure, combined with the crystal refinement effect induced by the composite nucleating agent, achieves a dual stiffening mechanism of "molecular chain-crystalline state". This not only endows the material with resistance to strong alkali corrosion, but also synergistically improves the material's heat distortion temperature.

[0043] (4) In the preparation method of the nylon material of the present invention, the premixed material is added from the main feed port of the twin-screw extruder, and the epoxy chain extender is added from the side feed port of the twin-screw extruder. This can effectively avoid problems such as excessive melt viscosity, poor plasticization, and material carbonization caused by premature over-reaction of the chain extender; at the same time, the degree of in-situ chain extension reaction can be precisely controlled, so that the nylon molecular chains grow moderately and form a uniform and slightly branched structure. Combined with the grain-refining effect of the composite nucleating agent of the present invention, the high-temperature rigidity and dimensional stability of the material can be improved from both the molecular structure and crystal morphology dimensions. Moreover, the reaction conditions are mild throughout the process, which can preserve the alkali resistance and toughness of the long carbon chain nylon substrate to the greatest extent.

[0044] In summary, the composite nucleating agent of this invention can improve the long-term stability of nylon materials in strongly alkaline environments. Furthermore, the composite nucleating agent of this invention can be used to increase the heat distortion temperature of nylon materials and improve their resistance to alkali corrosion. Even further, the nylon material of this invention exhibits good heat resistance and resistance to strong alkali corrosion. Still further, the preparation method of the nylon material of this invention is simple and convenient, and the obtained nylon material possesses excellent comprehensive mechanical properties, heat distortion temperature, and resistance to alkali corrosion. Detailed Implementation

[0045] The present invention will be further described below with reference to specific embodiments, but the scope of protection of the present invention is not limited thereto.

[0046] The testing method in this invention is described below: (1) Crystallinity: Differential scanning calorimetry (DSC) was used for testing under nitrogen atmosphere at a heating rate of 10℃ / min, with a testing range of -50 to 250℃. The mass crystallinity was calculated using the formula Xc = ΔH based on the enthalpy of fusion of the second heating curve. m / (ΔH) m 0 ×w)×100%, where ΔH m The enthalpy of melting of the sample, ΔH m 0 ν is the enthalpy of fusion of 100% crystalline nylon 612 (taken as 230 J / g), and w is the mass fraction of the matrix resin.

[0047] (2) Heat distortion temperature: Tested according to GB / T1634.2-2019, using the bending load method, with a sample size of 80mm×10mm×4mm, a bending stress of 1.80MPa, a heating rate of 120℃ / h, and the temperature when the bending deformation of the sample reaches 0.34mm is recorded.

[0048] (3) Tensile strength: Tested according to GB / T1040.2-2006, the specimen is a type I dumbbell, the tensile rate is 50 mm / min, and the test temperature is 23℃.

[0049] (4) Notched impact strength: Tested in accordance with GB / T1843-2008, using a cantilever beam notched impact test, with a sample size of 80mm×10mm×4mm, notch type A, and test temperature of 23℃.

[0050] (5) Alkali resistance tensile strength retention rate: Immerse the tensile specimen in a 45% KOH aqueous solution, seal it and place it in an 85℃ constant temperature oven for 168h; after taking it out, rinse it with deionized water until neutral, dry it and test the tensile strength according to the above method; calculate according to the formula: alkali resistance tensile strength retention rate = tensile strength after alkali corrosion / original tensile strength × 100%.

[0051] (6) Alkali-resistant impact strength retention rate: Immerse the impact sample in a 45% KOH aqueous solution, seal it and place it in an 85℃ constant temperature oven for 168h; take it out, rinse and dry it, and test the notched impact strength according to the above method; calculate according to the formula: Alkali-resistant impact strength retention rate = impact strength after alkali corrosion / original impact strength × 100%.

[0052] (7) Alkali creep resistance test: The material is injection molded into a simulated battery sealing ring sample, assembled into a simulated alkaline manganese battery structure, injected with KOH electrolyte with a mass fraction of 45%, sealed and stored in an environment of 60°C and 85% relative humidity; observe the contact surface between the sealing ring and the shell every week to see if alkaline creep, whitening and cracking occur, and record the number of storage weeks when the first alkaline creep phenomenon occurs.

[0053] In the following examples and comparative examples, all raw materials used were commercially available products. Among them, the hindered phenolic antioxidant, Antioxidant 1098, was purchased from BASF AG, Germany; the copper salt, Brüggemann H3336, was purchased from Brüggemann AG, Germany; and the organically modified montmorillonite, DK5, was purchased from Zhejiang Fenghong New Material Co., Ltd.

[0054] Unless otherwise specified, all parts in the embodiments and comparative examples of the present invention are expressed in parts by weight.

[0055] Examples 1-6 and Comparative Examples 1-9 (1) Weigh the raw materials according to the formulas in Table 1 and Table 2, and place the matrix resin at 90°C for vacuum drying for 6 hours to obtain the dried matrix resin. (2) The nucleating agent, alkali-resistant stabilizer, processing aid and dried matrix resin are placed in a high-speed mixer and mixed to obtain a premix; (3) The premixed material is added from the main feed port of the twin-screw extruder, and the epoxy chain extender is added from the side feed port of the twin-screw extruder. After melt blending, the mixture is extruded, water-cooled, and pelletized to obtain nylon material.

[0056] In step (1), the moisture content of the dried matrix resin is ≤0.15%; in step (2), the speed of the high-speed mixer is 400 rpm and the mixing time is 8 min; in step (3), the twin-screw extruder includes six sections: feeding section, compression section, melting section, venting section, mixing section and metering section, with the following temperatures: feeding section 210℃, compression section 220℃, melting section 235℃, venting section 240℃, mixing section 245℃, metering section 230℃; and die head temperature 235℃. The screw speed is 300 rpm; the epoxy chain extender is added from the side feed port of the 5th section (mixing section) of the twin-screw extruder.

[0057] Table 1

[0058] Table 2

[0059] Comparative Example 10 Except for the following steps, the rest are the same as in Example 1: The premix and epoxy chain extender are added together through the main feed port of the twin-screw extruder.

[0060] The nylon materials prepared in Examples 1-6 and Comparative Examples 1-10 were subjected to performance tests, and the test results are shown in Table 3.

[0061] Table 3

[0062] The test results of Examples 1-6 show that the composite nucleating agent provided by the present invention can increase the heat distortion temperature and improve the alkali corrosion resistance of nylon materials. The nylon materials prepared using the method of the present invention exhibit good comprehensive mechanical properties, heat distortion temperature, and alkali corrosion resistance; the heat distortion temperature is above 125℃, and the alkali corrosion resistance test can last up to 7 weeks.

[0063] Comparative Example 1, which did not add any composite nucleating agent, resulted in a significant decrease in the crystallinity of the nylon material to 13.6%, a heat distortion temperature of only 78℃, a decline in mechanical properties, a significant reduction in strength retention after alkali etching, and an alkali resistance test that could only be maintained for 4 weeks.

[0064] Comparative Example 2, with only the aromatic nucleating agent TCBT added and without the organically modified montmorillonite, produced a nylon material with a crystallinity of 16.4% and a heat distortion temperature of only 72℃. Although the strength retention rate after alkali etching was acceptable, the heat resistance decreased significantly, and the alkali creep resistance test lasted only 5 weeks. This demonstrates that using aromatic organic nucleating agents alone can only partially improve crystallization behavior. Without the two-dimensional nano-torsional permeability barrier constructed by the organically modified montmorillonite, the increase in heat distortion temperature is insufficient, and the improvement in alkali creep resistance is limited.

[0065] Comparative Example 3, which only added organically modified montmorillonite without adding aromatic nucleating agents, produced a nylon material with a crystallinity of 15.1%, a heat distortion temperature of 75℃, and maintained its alkali resistance for 5 weeks. This indicates that simply using organically modified montmorillonite can only provide partial physical barrier effects, lacking the crystallinity regulation effects of aromatic nucleating agents, such as spherulite refinement and compression of diffusion channels in amorphous regions. Therefore, the crystallinity improvement effect is limited, and the heat resistance and alkali resistance are far lower than those of the system using a composite nucleating agent.

[0066] The results of Comparative Example 2 and Comparative Example 3 together demonstrate that the aromatic nucleating agent is responsible for crystal state regulation, and the organically modified montmorillonite is responsible for nanoscale barrier. Both are indispensable and have a synergistic effect, rather than being a simple superposition of the properties of the two components.

[0067] Comparative Example 4 used unmodified ordinary montmorillonite instead of organically modified montmorillonite, resulting in a significant decrease in the properties of the nylon material. Its heat resistance and alkali resistance were far lower than those of the example samples. This indicates that ordinary montmorillonite has poor compatibility with the nylon matrix, making it difficult to achieve layered exfoliation and dispersion, and hindering the construction of effective nano-torsional diffusion paths. Furthermore, alkali penetration defects easily form at the filler-matrix interface, impairing the material's alkali resistance.

[0068] In Comparative Example 5, the mass ratio of TCBT to organically modified montmorillonite was 1:3, which exceeded the specified ratio range of this invention. The resulting nylon material exhibited decreased crystallinity and heat distortion temperature, and its alkali resistance test lasted only 5 weeks. This result indicates that when the proportion of aromatic nucleating agent is insufficient, the crystal refinement effect of the material is weakened, and the synergistic effect of the two components fails.

[0069] In Comparative Example 6, the mass ratio of TCBT to organically modified montmorillonite was 9:1, which also deviated from the recommended ratio. The resulting nylon material exhibited decreased overall performance and its alkali resistance test lasted for 5 weeks. This indicates that the amount of organically modified montmorillonite added was too low, resulting in insufficient nano-physical barrier and an inability to achieve a dual crystalline-nano protective effect.

[0070] Comparative Examples 5 and 6 together confirm that the mass ratio of aromatic nucleating agent to organically modified montmorillonite in the composite nucleating agent must be controlled at (2-4):1. If the proportion of either component is too high or too low, the synergistic effect between the two will be destroyed.

[0071] In Comparative Example 7, only long-chain nylon PA612 was used as the matrix resin, completely removing the semi-aromatic nylon component. The heat distortion temperature of the resulting nylon material dropped to 62°C, and the alkali creep resistance test was maintained for 5 weeks. This indicates that even with the composite nucleating agent of this invention, the heat resistance improvement of a single long-chain nylon system is still limited; blending long-chain nylon with semi-aromatic nylon can not only improve the heat resistance and rigidity of the material, but also produce a synergistic effect with the composite nucleating agent.

[0072] In Comparative Example 8, the crystallinity of the nylon material obtained after removing the epoxy chain extender SAG decreased to 13.6%, and the heat distortion temperature was 64℃. After alkaline etching treatment, the retention rates of tensile and impact strengths decreased significantly, and the alkali resistance test only lasted for 4 weeks. This confirms that the epoxy chain extender can achieve in-situ chain extension of nylon molecular chains, constructing a slightly branched structure to achieve stiffness enhancement. Together with the crystalline stiffness enhancement brought by the composite nucleating agent, it forms a dual stiffness enhancement mechanism of molecular chain-crystallization. After removing the epoxy chain extender, the high-temperature rigidity and long-term stability under strong alkaline conditions of the material both deteriorated significantly.

[0073] In Comparative Example 9, the nylon material obtained by removing the alkali-resistant stabilizer had a heat distortion temperature of 85℃, and its strength retention rate decreased significantly after alkali etching, with an impact strength retention rate of only 62%. The alkali creep resistance test lasted for 4 weeks. This indicates that the alkali-resistant stabilizer can inhibit the degradation of nylon molecular chains under strong alkali and high-temperature conditions, ensuring the retention rate of mechanical properties after alkali etching, and is an indispensable component in the formulation.

[0074] Comparative Example 10 showed that when the epoxy chain extender was added from the main feed port instead of the side feed port, the resulting nylon material had a heat distortion temperature of only 118℃, a significant decrease in notched impact strength, and poorer strength retention and alkali creep resistance after alkali corrosion. This demonstrates that adding the epoxy chain extender from the side feed port is a critical process condition; if added from the main feed port, the chain extender will prematurely undergo excessive reaction, resulting in abnormal melt viscosity, poor plasticization, uneven distribution of the branched structure of the nylon molecular chains, and ultimately impairing the material's toughness and alkali corrosion resistance.

[0075] This invention is not limited to the above-described embodiments. Any modifications, improvements, or substitutions that can be conceived by those skilled in the art without departing from the essential content of this invention fall within the scope of this invention.

Claims

1. A composite nucleating agent, characterized in that, It includes an aromatic nucleating agent and an organically modified montmorillonite, wherein the mass ratio of the aromatic nucleating agent to the organically modified montmorillonite is (2-4):

1.

2. The composite nucleating agent according to claim 1, characterized in that, The aromatic nucleating agent is selected from at least one of aromatic amide nucleating agents and aromatic acyl hydrazide nucleating agents; The organically modified montmorillonite can be selected from at least one of organic ammonium modified montmorillonite, amino acid modified montmorillonite, and polymer intercalated modified montmorillonite.

3. The composite nucleating agent according to claim 2, characterized in that, The aromatic amide nucleating agent is selected from at least one of 1,3,5-benzenetricarboxamides, aromatic diamides, and monoaromatic amides; wherein the aromatic diamide is selected from at least one of N,N'-dicyclohexylterephthalamide and N,N'-dicyclohexyl-2,6-naphthalenediamide. The aromatic acyl hydrazide nucleating agent is a bisbenzoyl hydrazide nucleating agent.

4. The composite nucleating agent according to claim 3, characterized in that, The composite nucleating agent is composed of the aromatic nucleating agent and the organically modified montmorillonite.

5. The application of a composite nucleating agent as described in any one of claims 1 to 4, characterized in that, The composite nucleating agent is used to increase the heat distortion temperature of nylon materials and improve their alkali resistance.

6. A nylon material, characterized in that, By weight, its raw material components include: 80-95 parts of matrix resin, 0.3-2 parts of epoxy chain extender, 0.2-1 parts of alkali-resistant stabilizer, and 0.5-3 parts of the composite nucleating agent as described in any one of claims 1-4; The matrix resin is a blend of long-chain nylon and semi-aromatic nylon in a mass ratio of (85-95):(5-15); the long-chain nylon is selected from at least one of nylon 612 and nylon 610; the semi-aromatic nylon is selected from at least one of poly(hexamethylene terephthalamide), poly(hexamethylene terephthalamide / poly(hexamethylene adipamide) copolymer, and poly(hexamethylene terephthalamide / poly(hexamethylene isophthalamide) copolymer.

7. The nylon material according to claim 6, characterized in that, The epoxy chain extender is selected from at least one of bisphenol A type epoxy resin and styrene-glycidyl methacrylate copolymer; The alkali-resistant stabilizer is a compound formed by hindered phenolic antioxidant and copper salt stabilizer in a mass ratio of 1:(1-2).

8. The nylon material according to claim 6, characterized in that, It also includes 0.1 to 0.8 parts of processing aids; the processing aids are selected from at least one of calcium stearate, zinc stearate, silicone, pentaerythritol stearate, and ethylene bis-stearamide.

9. The method for preparing nylon material according to any one of claims 6 to 8, characterized in that, Includes the following steps: (1) The composite nucleating agent, alkali-resistant stabilizer and dried matrix resin are mixed to obtain a premix; (2) The premixed material is added from the main feed port of the twin-screw extruder, and the epoxy chain extender is added from the side feed port of the twin-screw extruder. After melt blending, the mixture is extruded, water-cooled, and pelletized to obtain nylon material.

10. The method for preparing nylon material according to claim 9, characterized in that, The moisture content of the dried matrix resin is ≤0.15%; The temperature of each section of the twin-screw extruder is independently between 180 and 250°C, and the screw speed is between 200 and 350 rpm.

Citation Information

Patent Citations

  • Nylon 6 composition and preparation method and application thereof

    CN108587147A